2017
DOI: 10.1093/pm/pnw308
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Pain in Male and Female Iraq/Afghanistan-Era Veterans: Associations with Psychiatric Symptoms and Functioning

Abstract: Although female Iraq/Afghanistan-era veterans reported higher levels of pain than male veterans overall, male and female veterans experienced similar levels of psychiatric and functional problems at equivalent levels of reported pain. These findings suggest that pain-associated psychological and functional impacts are comparable and consequential for both male and female veterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
5
10
0
Order By: Relevance
“…Significant correlation was not detected between clinical pain intensity ratings and slow-5 power (Correlation (r): − 0.04 to 0.23). While a trend towards higher (relative to the low pain FOP group) power in the slow-4 sub-band (Channel C10) for the high pain FOP cohort was observed, a significant intergroup difference was not present (p = 0.137) pain conditions in women [31,47]. Additionally, slightly higher pain levels were measured in older FOP patients relative to younger patients; an observation that was previously observed in other rare musculoskeletal conditions [21].…”
Section: Discussionsupporting
confidence: 51%
“…Significant correlation was not detected between clinical pain intensity ratings and slow-5 power (Correlation (r): − 0.04 to 0.23). While a trend towards higher (relative to the low pain FOP group) power in the slow-4 sub-band (Channel C10) for the high pain FOP cohort was observed, a significant intergroup difference was not present (p = 0.137) pain conditions in women [31,47]. Additionally, slightly higher pain levels were measured in older FOP patients relative to younger patients; an observation that was previously observed in other rare musculoskeletal conditions [21].…”
Section: Discussionsupporting
confidence: 51%
“…The definite mechanism underpinning the association between female sex and higher prevalence of the musculoskeletal pain remains poorly understood. The sex‐specific association with pain may be related to the willingness to disclose since women report more pain than men [34]. Moreover, laboratory research did not produce a robust evidence for the sex differences in human pain sensitivity of healthy individuals [35].…”
Section: Discussionmentioning
confidence: 96%
“…mental health study of 3,000 Operation Enduring Freedom and Operation Iraqi Freedom veterans, women reported significantly higher intensity from headache, pain, and muscle soreness (Naylor et al, 2017). Gradus et al (2017) found that women who received a diagnosis of post-traumatic stress disorder (PTSD) and had a history of alcohol abuse or dependence were more likely than men to engage in nonfatal intentional self-harm.…”
mentioning
confidence: 99%